Practices and Determinants of Household Solid Waste Management: A Cross-Sectional Study in Urban Karnataka, South India - Abhiharshan SB; Samudyatha UC (National Journal of Community Medicine, 2025)
Introduction: Scientific and sustainable household solid waste management is crucial in achieving SDG 12 (responsible consumption) and SDG 3 (good health). Poor waste practices can harm both the environment and people's health. Objective: To assess the solid waste management practices and its association with sociodemographic profile of households in a selected urban locality of Kolar, in South India. Methods: A cross-sectional study was conducted from April to June 2023, covering 318 consecutively sampled urban households, using a validated semi-structured questionnaire to collect data. Results: The majority (28.6%) of households were from the lower middle socioeconomic class. Food and kitchen waste, plastics, and paper waste were the most common types of waste generated. Sanitary napkins/pads were disposed of with plastic waste without segregation. Closed containers were used for wet waste storage in 64.8% of households. Households with children under 5 years were more likely to use closed containers (OR: 2.04, 95% CI: 1.18-3.50). Sanitary disposal of waste was practiced by 64.4% of households, with higher odds in households located along main roads. Conclusion: This study found high waste segregation rates but poor sanitary waste management so this recommends a multi-faceted approach to improve waste management. Urban governance should adopt a circular waste management approach to improve accountability and resource efficiency.